Penerapan Naïve Bayes pada Potensi Akademik Siswa SD Negeri 5 Singakerta - Ni Kadek Winda Patrianingsih; I Kadek Arya Sugianta (UIN Sunan Kalijaga Yogyakarta, 2023)
Student potential cannot only be measured based on the result of academic scores, and many things influence student academic determination. The purpose of this research is to prove that students' potential is influenced by many things, such as character, academic activity, socioeconomic status, and distance of residence. By using the naïve Bayes method and testing with the confusion matrix, it will give results for this research. The data is from V-grade students at SD Negeri 5 Singakerta, with 120 students assisted by the homeroom teacher. Based on the results of the tests that have been carried out using a data sample of 10 students and 1 data using the Naïve Bayes, it is obtained that students have academic potential, and the results with the confusion matrix are accuracy of 75%, precision of 81%, and recall of 89%. In this case, it can be concluded that the academic potential of students can not only be measured based on the results of the final grade, but many other factors have an effect, the application of the Naïve Bayes in students' academic potential is appropriate to use.